Peningkatan Pengetahuan Tentang Pemberantasan Sarang Nyamuk Di SMK Cipta Semesta Indonesia - Marius Jati; Sunaryo (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Community Service activities have been carried out in the form of health counselling on the Prevention of Mosquito Nest Eradication at Citra Semesta Indonesia Health Middle School, Wates, Kulonprogo. The high number of DHF cases that occurred in Kulonprogo Regency is a major concern in this extension program. This activity was carried out on June 8 2022 in Classroom XII of Cipta Semesta Indonesia Vocational School. This community service program method uses lectures with video-assisted presentations. Also accompanied by sharing experiences regarding the Prevention and Eradication of Mosquito Nests. The results of the activity showed that after being given counselling, the percentage of teenagers who answered correctly increased by 85% (correct score <10), 80% (10 â‰¤ Correct score â‰¤ 15), and 93.33% (correct score> 15). The number of participants who took part on the day of implementation was 32 students. Counselling that has been done can increase knowledge about Eradicating Mosquito Nests in SMK students